THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE ABOUT CIGARETTES AND SMOKING BEHAVIOR AMONG STUDENTS IN THE WORKING ARE OF THE SERING HEALTH CENTER UPT, MEDAN CITY - Eyanoer, Putri Chairani; Simanjuntak, Novita Hasiani; Hutagalung, Angeline Kory; Tampubolon, Johana Bonafide; Hulu, Dirga Agustina; Simanullang, Putri Andriani; Halawa, Pisces Alfred Dorifman (Jurnal Mutiara Kesehatan Masyarakat, 2025)
The increasing intensity of digital technology use has raised concerns about its impact on the social development of the younger generation. This study focused on analyzing the causal relationship between the frequency of social media use and social interaction skills among Vocational High School (SMK) students in urban areas. An observational analytical study with a prospective cohort study design was conducted at SMK Teknologi Abadi, Central Jakarta, from January to May 2025. A total of 105 eleventh-grade students were involved in this study, selected using a stratified random sampling method based on major. Data were collected through social media usage time logs (obtained through a third-party application) and the standard Social Skills Rating System (SSRS) questionnaire. Data were processed using IBM SPSS software version 26.0, including binary logistic regression analysis and odds ratio tests with a significance level of $p < 0.05$. The study findings showed that the majority of students (72.4%) recorded social media use above the normal limit (more than 3 hours per day), and 65.7% of them were categorized as having low social interaction skills. Statistical analysis proved a significant and strong association between excessive social media use and low social interaction skills ($OR = 2.85; p = 0.003$), meaning students who spend more time on social media are 2.85 times more likely to experience a decline in their ability to interact face-to-face. In conclusion, excessive social media use has a clear negative impact on the quality of adolescents' social interactions, underscoring the urgency of digital literacy education and strengthening offline social activities in schools.